KAJIAN REKRUTMEN KARANG DI ZONA INTI DAN ZONA PEMANFAATAN TERBATAS KAWASAN KONSERVASI PULAU PIEH - Utama, Agung Putra; Suparno, Suparno; Damanhuri, Harfiandri (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2025)
This study aimed to assess coral recruitment conditions and genus diversity in the core zone and limited use zone of the Pieh National Marine Conservation Area, West Sumatra. A quantitative descriptive method was employed, using 1x1 meter quadrat transects at ten observation stations. Observed parameters included the number of coral recruits and genus identification. The results showed that average coral recruitment in the core zone was categorized as very low (1.84 ind/m²), while the limited use zone reached a low category (2.83 ind/m²), with one station (Limited Use Zone 3) showing high recruitment (7.33 ind/m²). The dominant coral genera in both zones were Pocillopora and Porites, while the limited use zone exhibited higher genus diversity (12 genera) compared to the core zone (10 genera). This study highlights that coral recruitment success is not solely determined by conservation zone status, but is also strongly influenced by microhabitat conditions and local environmental factors. The findings serve as a scientific reference for data-driven management of marine conservation areas to support coral reef ecosystem sustainability.